Content analysis of stem-focused education research in Turkey - Çevik, Mustafa (Journal of Turkish Science Education, 2017)
This study conducted a content analysis for science, technology, engineering and mathematics (STEM)focused studies in the field of education between 2014 and 2016 in Turkey. “Publication Classification Form” was used to analyze 34 articles identified in this context. The articles were examined by conducting content analysis including identity of the article, its subject, its methodology, its data collection instruments, its sample and data analysis methods. Based on the obtained data, it was determined that the most publications were made by scholars working in institutions such as the Ministry of National Education, Gazi, Sinop, Marmara and Middle East Technical University. It was also found out that qualitative method-based studies were the most prevalent in researches. In the analysis of the data, it was determined that descriptive analyzes were mainly performed, content and descriptive analyzes involving qualitative research methods were extensively used in the studies. It was concluded that analyzing the studies helped researchers make appropriate decisions about the research processes and observe trends in STEM-focused researches.
Keywords: Content analysis; STEM education; STEM research